Advances in gene therapy for respiratory diseases 1 - Engelhardt, John F. (Henry Stewart Talks, 2023)
Human lung epithelia, Proximal airway and distal conducting epithelial cell types, Inherited and acquired lung diseases, Stem cell targets for gene editing, Gene transfer and gene editing, Cystic Fibrosis (CF), Animal models of CF, Comparative airway cell biology, CFTR gene transfer for CF